Characterization of acclimation of Hordeum vulgare to high irradiation based on different responses of photosynthetic activity and pigment composition - Kurasová, Irena; Cajánek, Martin; Kalina, Jirí; Urban, Otmar; Spunda, Vladimír (Photosynthesis research, 2002)
The ability of spring barley (Hordeum vulgare cv. Akcent) to adjust the composition and function of the photosynthetic apparatus to growth irradiances of 25-1200 mumol m(-2) s(-1) was studied by gas exchange and chlorophyll a fluorescence measurements and high-performance liquid chromatography. The increased growth irradiance stimulated light- and CO(2)-saturated rates of CO(2) assimilation expressed on a leaf area basis up to 730 mumol m(-2) s(-1) (HL730), whereas at an irradiance of 1200 mumol m(-2) s(-1) (EHL1200) both rates decreased significantly. Further, the acclimation to EHL1200 was associated with an extremely high chlorophyll a/b ratio (3.97), a more than doubled xanthophyll cycle pool (VAZ) and a six-fold higher de-epoxidation state of the xanthophyll cycle pigments as compared to barley grown under 25 mumol m(-2) s(-1) (LL25). EHL1200 plants also exhibited a long-term inhibition of Photosystem II (PS II) photochemical efficiency (F (v)/F (m)). Photosynthetic capacity, chlorophyll a/b and VAZ revealed a linear trend of dependence on PS II excitation pressure in a certain range of growth irradiances (100-730 mumol m(-2) s(-1)). The deviation from linearity of these relationships for EHL1200 barley is discussed. In addition, the role of increased VAZ and/or accumulation of zeaxanthin and antheraxanthin in acclimation of barley to high irradiance is studied with respect to regulation of non-radiative dissipation and/or photochemical efficiency within PS II.